Implementasi Building Information Modelling 3D, 4D, dan 5D pada Pembangunan Masjid Dodik Latpur Amborawang - Yosef Metrio; Purwantoro, Almuntofa; Dewantoro (Civil Engineering of Universitas Islam Nahdlatul Ulama Jepara, 2025)
This study aims to analyze the implementation of 3D, 4D, and 5D Building Information Modeling (BIM) in the construction project of the Dodik Latpur Mosque in Amborawang, East Kalimantan. The method used is a quantitative approach with data analysis using Graphisoft ArchiCAD, CYPE Open BIM Quantities, and Microsoft Project software. The results of the study indicate that the application of BIM significantly improves the accuracy of planning and cost estimation, with the Cost Estimate (RAB) calculated at Rp. 2,180,960,541.24, showing a difference of 2.54% compared to the conventional method. Additionally, the project duration was reduced by 14 days, with a total time of 168 days. The study concludes that BIM integration not only improves accuracy and efficiency in project management but also strengthens collaboration among stakeholders. These findings are expected to make a significant contribution to the adoption of BIM technology in the Indonesian construction industry.